The political economy of the landscape of trade unions in Bangladesh: The case of the RMG sector - Hassan, Mirza M; Aziz, Syeda Salina; Rahemin, Raeesa; Khan, Insiya; Hoque, Rafsanul (BIGD, 2024)
The paper explores the political economy landscape of trade unionism in Bangladesh. The focus is on the Ready-Made Garments (RMG) sector, where trade unions (TU) are highly salient and relatively more operational because of the sector’s economic importance, numerical strength of the labour, high degree of concentration of the industries, and TU’s global network, among other factors. Relying predominantly on primary data, we look at both the formal and informal dimensions of industrial relations and their implications for the state-capital-labour interactions as well as governance of TUs. Literature on RMG-related TUs in Bangladesh generally examines it from a social movement perspective. We take a slightly different approach in this paper by making a modest attempt to fulfil the knowledge gaps in TU research. We do this by exploring the formal and informal aspects of relations between the regulatory institutions and the TUs and, more importantly, the internal governance of the TUs themselves as noted above. Additionally, we explore the two-way relational dynamics of TU leaders and the garment workers. These areas have not received much attention in the extant literature. By adopting a politico-sociological perspective, the paper reflects on the collective action dynamics of industrial labour in the context of the global south.